PENGARUH KOMPETENSI, INDEPENDENSI DAN PROFESIONALISME TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT PROVINSI RIAU - Handayani, Silvi; Kamaliah, Kamaliah; Rasuli, M. (Jurnal Ekonomi, 2014)
This study aims to test the Influence of Competence, Independence and Professionalism on Audit Quality Inspectorate officers of Riau Province. The sampling method using a census because the total population is less than 100.The author conducted research through questionnaires that are sent to respondances. Author used Multiple regretion methode in analysing the data, which its independent variables are competence (X1), independence (X2) and profesionalism (X3), thus its dependent variable is audit quality (Y). Multiple regretion model was tested which coefficient of determination (R2), F test and t test and the data is processed with the statistical program SPSS 17.00.Based on research found that tvalue for every variables X1, X2 and X3 are 9.101, 2.306, and 1.691 with ttable is 2,024, its show that tvalue more than ttable in term of competence and independence, whereas professionalism show that tvalue less than ttable. These values show that competence and independence variables have significant influences to quality of audit of Inspectorate officers Riau Province. Whereas professionalism variable does not have significant influence to quality of audit of Inspectorate officers Riau Province. Therefore, based on the research R value is 0,836 with adjusted R2 is 0,676. Value of the coefficient of determination indicates that the competence, independence, and professionalism contribute to the dependent variable (quality audit) of 67,6%, while the remaining 32,4% are influenced by other outside factor model